ORION ONE: MENGHIDUPKAN KEMBALI PLAZA DENGAN REVITALISASI DAN URBAN AKUPUNTUR - Matthew Matthew; J.M. Joko Priyono Santoso (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Plaza Orion was originally a cinema building, Cinema Orion was built in the 1920 by the Dutch. Now the cinema building has been converted into an electronic shop building, still using its original name, namely Plaza Orion. After the riots, most of the electronic merchants migrated to several places and what can be seen is the Mangga Dua electronic area. Plaza Orion is a physically and functionally degraded building, even though the area and location can be a support for Plaza Orion itself. The problem that will be overcome is to revive Plaza Orion functionally and adapt to its environment in the flooded area so that it can come back to life and can become a cornerstone to support the surrounding area in terms of the advancement of electronic technology. The main objective of this final project is to restore the glory of Plaza Orion in terms of facilities, quality and number of visitors by using qualitative and comparative methods. So that Plaza Orion can become a supporter of the sector area of technology and electronics advancement. By keeping abreast of the times in adapting to online learning. There must be an injection of revitalization based on urban acupuncture at Plaza Orion so that it can come back to life and can become a center for the advancement of electronic technology and become a supporter of nearby area as well as for the Glodok community and surrounding areas. By using a revitalization method based on urban acupuncture, it provides an opportunity to revive Plaza Orion. Keywords: Electronic; Revitalization; Technology; Urban acupuncture Abstrak Plaza Orion awalnya merupakan gedung bioskop, Cinema Orion yang dibangun tahun 1920-an oleh Belanda. Sekarang gedung bioskop itu berubah fungsi menjadi gedung pertokoan elektronik, masih menggunakan nama awalnya, yaitu Plaza Orion. Setelah kejadian kerusuhan sebagian besar dari pedagang elektronik melakukan migrasi kebeberapa tempat dan yang dapat dilihat seperti area elektronik mangga dua. Plaza Orion merupakan bangunan yang terdegratasi secara fisik dan fungsi, padahal area kawasan dan lokasi dapat menjadi sebuah pendukung dari Plaza Orion sendiri. Permasalahan yang akan diatasi adalah membangkitkan kembali Plaza Orion secara fungsi dan beradaptasi degan lingkunganya yang berada diwilayah banjir agar dapat menjadi hidup kembali serta dapat menjadi penjuru untuk mendukung area sekitarnya dari segi bidang kemajuan teknologi elektronik. Tujuan utama dari tugas akhir ini untuk mengembalikan kejayaan dari Plaza Orion dari segi fasilitas, kualitas serta jumlah pengunjung dengan menggunakan metode kualitatif dan kompartif. Agar Plaza orion dapat menjadi pendukung dari area sektor dari bidang kemajuan teknologi dan elektronik. Dengan memegang mengikuti perkembangan zaman dalam beradaptasi dengan pembelajan online. Harus adanya suntikan revitalisasi didasari urban akupuntur pada Plaza Orion agar dapat menjadi hidup kembali serta dapat menjadi pusat kemajuan teknologi elektronik dan menjadi pendukung area sekitarnya serta untuk untuk wilayah masyarakat Glodok dan sekitar area wilayahnya. Dengan menggunakan metode revitalisasi yang didasari dengan urban akupuntur memberikan peluang untuk membangkitkan Plaza Orion.